2012
DOI: 10.1163/15685373-12342072
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Bias, Executive Control and Information Processing Speed

Abstract: This study examined the relationships between processing speed and Implicit Association Test (IAT) performance using a race and a socially neutral IAT, in 51 European American adults ranging in age from 19 to 55. Simple reaction time was not correlated with IAT performance. However, faster higher-level processing speed on a 3-back task was correlated with lower transformed scores and shorter latencies on multiple implicit association race and neutral measures. Higher-level processing may account for approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Further, Salvatore (2013) appeared to be under the impression that we are unfamiliar with prejudice research. In our previous work, we have used a wide array of methodologies to assess prejudice (e.g., Conley, Rabinowitz, & Hardin, 2010;Conley, Ziegler, & Moors, 2013;Diamond et al, 2012), but in our target article, we were primarily interested in assessing only explicit prejudice. Although follow-up studies are needed to address the nuanced questions raised by some of the commentators, we do not believe that researchers need to replicate every theoretical process once a new target group emerges in the literature.…”
Section: At the Operational Level: Future Methodological Considerationsmentioning
confidence: 99%
“…Further, Salvatore (2013) appeared to be under the impression that we are unfamiliar with prejudice research. In our previous work, we have used a wide array of methodologies to assess prejudice (e.g., Conley, Rabinowitz, & Hardin, 2010;Conley, Ziegler, & Moors, 2013;Diamond et al, 2012), but in our target article, we were primarily interested in assessing only explicit prejudice. Although follow-up studies are needed to address the nuanced questions raised by some of the commentators, we do not believe that researchers need to replicate every theoretical process once a new target group emerges in the literature.…”
Section: At the Operational Level: Future Methodological Considerationsmentioning
confidence: 99%
“…In this line, it is worth noting that the flanker task adaptation by Bidet-Ildei and Bouquet [ 25 ] already suggested that the gender of the avatar influenced target recognition. Preceding studies have discussed the possible interaction between implicit biases and executive functions [ 65 , 66 ], but the unclear picture obtained so far may well be the result of the use of laboratory tasks with static representations of non-human elements in non-immersive contexts. Future VR adaptations of these and other related tasks could overcome these limitations regarding the naturality and plausibility of the stimuli and contexts.…”
Section: Discussionmentioning
confidence: 99%